POLA INTERAKSI SISWA PENGGUNA GADGET DI MAN 2 KOTA BOGOR - Pauziah, Siti (Sosial Horizon: Jurnal Pendidikan Sosial, 2022)
Advances in information technology, especially gadgets, have now entered all aspects of human life, if you pay attention at this time almost all walks of life have used gadgets, especially teenagers because they are considered to be able to affect the interaction patterns of users. The purpose of this research is to find out how the interaction patterns formed by students using gadgets are within the scope of student interactions in the school environment. This research method uses a qualitative case study approach. carried out at MAN 2 Bogor City from January to April 2022, the primary sources are students, data collection by observation and observasi and interviews is validated by triangulation of sources, analyzed through the stages of data collection, data reduction, data display and conclusion drawing. The results of this study indicate the interaction pattern of students using gadgets in MAN 2 Bogor city; interaction through media that is used as a tool to exchange information, focus on each gadget, individual interaction between groups, interactions that occur through online games, cooperation between friends through whatsapp groups, being alone (individual).